Five new species of the genus Andes Stål, 1866 from China (Hemiptera, Fulgoromorpha, Cixiidae) - Wang, Xiao-Ya; Zhi, Yan; Chen, Xiang-Sheng (European Journal of Taxonomy, 2022)
Five new species of the genus Andes Stål, 1866, A. balteiformis Wang, Zhi & Chen sp. nov., A. bifidus Wang, Zhi & Chen sp. nov., A. furcutus Wang, Zhang & Chen sp. nov., A. latanalus Wang & Chen sp. nov. and A. pallidus Wang & Chen sp. nov. from China, are described and illustrated. A key to the species of Andes in China is provided.